2019
DOI: 10.1002/ccd.28283
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of quantitative flow ratio in prospectively enrolled patients: An individual patient‐data meta‐analysis

Abstract: Objectives We aimed to provide robust performance estimates for quantitative flow ratio (QFR) in assessment of intermediary coronary lesions. Background Angiography‐based functional lesion assessment by QFR may appear as a cost saving and safe approach to expand the use of physiology‐guided percutaneous coronary interventions. QFR was proven feasible and showed good diagnostic performance in mid‐sized off‐line and on‐line studies with fractional flow reserve (FFR) as reference standard. Methods We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 25 publications
7
72
1
1
Order By: Relevance
“…Additionally, we showed that QFR may be useful for appropriate evaluation of visually estimated severe lesions not applicable for FFR measurement. The current findings add to the existing knowledge that QFR agrees with wire-based FFR in the majority of patients in head to head comparisons [5,6,11,16]. We found a low sensitivity of QFR and FFR when CMR and MPS were used as reference.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, we showed that QFR may be useful for appropriate evaluation of visually estimated severe lesions not applicable for FFR measurement. The current findings add to the existing knowledge that QFR agrees with wire-based FFR in the majority of patients in head to head comparisons [5,6,11,16]. We found a low sensitivity of QFR and FFR when CMR and MPS were used as reference.…”
Section: Discussionsupporting
confidence: 76%
“…ree previous meta-analyses assessed the diagnostic parameters of QFR for detecting significant coronary stenosis. e reliability of the analysis may have been affected by the lack of current studies and the inclusion of a conference abstract [7,11,12]. Another meta-analysis included 4 well-designed multicenter prospective studies, in which the QFR calculation followed a strict procedure and finished by well-trained operators, but the study sample was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis included 4 well-designed multicenter prospective studies, in which the QFR calculation followed a strict procedure and finished by well-trained operators, but the study sample was relatively small. It may be that the diagnostic performance of QFR in clinical practice is difficult to ascertain because it relies on clinical staff for accuracy and there are different protocols in each setting [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations